The Australian mathematics curriculum: A move forward or back to the future? - Atweh, Bill; Goos, M. (Australian Council for Educational Research, 2011)
The release of the “Australian curriculum: Mathematics” has generated considerable debate in the education community. Some educators warn that this debate has centred on mathematical content and skills, setting the conditions for a 'back to basics' movement in line with the political rhetoric that accompanied the national curriculum development. But the “Shape of the Australian curriculum: Mathematics” document contains a commitment to provide a futures-oriented curriculum. This article provides a critical analysis of the released curriculum document in the light of these claims. It questions whether the direction taken in the curriculum demonstrates a futuristic view of mathematics education. It considers whether the document is aligned with a national focus on education for citizenship, identified in past government declarations on education as the basis for the development of the national curriculum, and the role of technology in teaching mathematics based on decades of theorising and research in this area.